Guatemala : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guatemala. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that a sound monetary policy management in Guatemala has helped keep inflation expectations firmly anchored. Fiscal deficits have remained at decade lows on the back of low debt tolerance and inadequate budgetary execution. Terms of trade gains and an upsurge in remittances inflows moved the current account into a sizable surplus. The financial system is sound and well-regulated while vulnerabilities seem manageable. Growth performance nevertheless falls shorts of the rates needed to achieve Guatemala's aspirations to meaningfully lift the living standards of its citizens. Near-term growth prospects remain subdued, at 3.2 percent in 2018 and 3.6 percent in 2019.